2014
DOI: 10.1039/c3cp54714k
|View full text |Cite
|
Sign up to set email alerts
|

Promising electrochemical hydrogen storage properties of thick Mg–Pd films obtained by insertion of thin Ti interlayers

Abstract: In this paper, the structures of 500 nm thick Mg-Pd films were tailored by insertion of 1 nm thin Ti interlayers, and their electrochemical hydrogen storage properties were investigated. Results showed that thin Ti interlayers in the Mg bulk film could significantly improve the discharge properties of thick Mg-Pd films. The Mg100-Ti1 sample exhibited the most promising electrochemical properties, including a shorter activation period, larger discharge capacity, superior cyclic stability and high rate discharge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 30 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…5 Mo (molybdenum) exhibits a high solubility (about 35 at%) in γ-U at high temperatures over 833 K. Below this temperature, however, Mo-dissolved γ-U alloy will be decomposed into U 2 –Mo and α-U. 6,7 A previous study has suggested that U alloyed with Mo can stabilize its bcc structure at low temperatures. 8 U–Mo alloys having a molybdenum concentration of 6–10 wt% are considered the most promising candidates for fuels.…”
Section: Introductionmentioning
confidence: 99%
“…5 Mo (molybdenum) exhibits a high solubility (about 35 at%) in γ-U at high temperatures over 833 K. Below this temperature, however, Mo-dissolved γ-U alloy will be decomposed into U 2 –Mo and α-U. 6,7 A previous study has suggested that U alloyed with Mo can stabilize its bcc structure at low temperatures. 8 U–Mo alloys having a molybdenum concentration of 6–10 wt% are considered the most promising candidates for fuels.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Compared with the gas cylinders, metal hydrides have attracted lots of attention around the world due to the advantages of much higher volume density (70-150 kg m À3 ), more satisfying safety performance, much higher hydrogen purity, and much lower moderate operating conditions. [3][4][5][6][7][8][9][10][11][12] In recent years, the La-Mg-Ni based hydrogen storage alloys, especially the alloys with superlattice structures of AB 3 -, A 2 B 7and A 5 B 19 type, have been a focus of studies. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] These structures possess characteristic layered structure consisting of one MgZn 2 -type (A 2 B 4 ) cell and one to three CaCu 5 -type (AB 5 ) cells stacking along c-axis, which are considered as the promising candidates to replace current AB 5 -type alloys as negative electrodes of MH-Ni batteries.…”
Section: Introductionmentioning
confidence: 99%